The Ramayana Trail and the Mediatization of Materiality in the Relationship between Myth and History - Albrecht, Jessica (Journal of Religion, Media and Digital Culture, 2025)
This article examines the mediatization/mediation of the Ramayana epic in Sri Lanka and its use in constructing narratives of authenticity through material sites and digital platforms. Traditionally depicted as a demon king, in the last decades Ravana has been reinterpreted as the Hela king, symbolizing an ancient Sri Lankan history distinct from Indian influences. This narrative shift is supported by the Ramayana Trail, a collaborative initiative between the Sri Lankan and Indian governments, which uses archaeological and natural sites to substantiate claims of the epic’s historical reality. Through a digital ethnographic analysis, this study explores how social media platforms like Instagram contribute to the popularization and reinforcement of these narratives, merging digital representations with physical locations to create affective experiences of authenticity. The promotion of the Ramayana Trail serves as both a political tool and a strategy for cultural diplomacy, reinforcing national identities while often marginalizing Tamil narratives and alternative histories. This research highlights the role of mediation/mediatization in shaping collective memory and the complex intersections of heritage, politics, and identity in contemporary Sri Lanka.
CRIS-Team Scopus Importer:2025-08-22
Keywords: India; Mythmaking; Ramayana; Ravana; Sri Lanka; travel